2020
DOI: 10.1371/journal.pone.0238876
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and validation of early genetic biomarkers for apple replant disease

Abstract: Apple replant disease (ARD) is a serious threat to producers of apple trees and fruits worldwide. The ARD etiology is not unraveled and managing options are either economically not applicable or environmentally harmful. Thus, interest is given in biomarkers that allow to indicate ARD situations at early time points in order to classify soils according to ARD severity but also to analyze the effectiveness to potential countermeasures. This study aimed at (i) identifying ARD biomarkers on the transcriptional lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 67 publications
2
19
1
Order By: Relevance
“…However, a relationship between ARD severity and the production of terpenoid phytoalexins in the plant has not been observed to date. Several studies on ARD demonstrated remarkably higher contents of biphenyl and dibenzofuran phytoalexins in plants cultivated in ARD soils compared to disinfected ARD soils ( Winkelmann et al, 2019 ; Reim et al, 2020 ; Rohr et al, 2020b ; Balbin-Suarez et al, 2021 ; Busnena et al, 2021 ). However, Reim et al (2020) showed that the genes coding for biosynthesis of these phytoalexins were more strongly induced in the susceptible rootstock ‘M9’ than in the ARD tolerant genotype Mr5, indicating that these phytoalexin compounds do not help against ARD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a relationship between ARD severity and the production of terpenoid phytoalexins in the plant has not been observed to date. Several studies on ARD demonstrated remarkably higher contents of biphenyl and dibenzofuran phytoalexins in plants cultivated in ARD soils compared to disinfected ARD soils ( Winkelmann et al, 2019 ; Reim et al, 2020 ; Rohr et al, 2020b ; Balbin-Suarez et al, 2021 ; Busnena et al, 2021 ). However, Reim et al (2020) showed that the genes coding for biosynthesis of these phytoalexins were more strongly induced in the susceptible rootstock ‘M9’ than in the ARD tolerant genotype Mr5, indicating that these phytoalexin compounds do not help against ARD.…”
Section: Discussionmentioning
confidence: 99%
“…Plants of the apple rootstock ‘M9’ and the wild apple genotype Malus ×robusta 5 (Mr5) accession MAL0991 were propagated in vitro via axillary shoots on a modified MS medium ( Murashige and Skoog, 1962 ; Rohr et al, 2020b ). Mr5 is known to be tolerant, whereas ‘M9’ is susceptible to ARD ( Reim et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our results provide a basis for employing a similar approach to other Streptomyces strains and species or other apple rootassociated organisms to comprehend the chemical basis of their ecological functions and interactions. It would also be useful to investigate the phenotypic and metabolic effect of ARD biomarkers such as phytoalexins (Reim et al, 2020;Rohr et al, 2020) and apple root exudates or compounds therein (e.g., phlorizin) on apple root-associated microorganisms and vice versa. Further investigations on the etiology of ARD as well as designing effective and sustainable biocontrol remedies must take into account both the molecular and the chemical networks between associated ecological partners in order to gain a holistic view.…”
Section: Insights Gained From the Chemical Evaluation Of Endophytic Smentioning
confidence: 99%